The water diviner - Crowe, Russell, 1964-; Courtney, Jai; Kurylenko, Olga, 1979-; Lucas, Isabel, 1985-; Hirschfelder, David (Burbank, CA : Warner Bros. Entertainment, 2015)
After the Battle of Gallipoli, an Australian man travels to Turkey to find his three missing sons.
Rental ready.
Anamorphic wide screen 1.78:1.
Camera, Andrew Lesnie ; editor, Matt Villa ; music, David Hirschfelder.
Jai Courtney, Olga Kurylenko, Russell Crowe, Isabel Lucas, Megan Gale.
MPAA rating: R.
Keywords: World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula -- Drama; Fathers and sons -- Drama; Fiction films; Feature films; Historical films